Исследование методов повышения надежности стеганосистем - Вакуленко, В. С. (ХНУРЭ, 2009)
This thesis is considered questions of reliability increase of the steganography systems. In the theses there are three methods offered – compression of information, change of code and modified method of replacement of LSB. Use of these methods is given by possibility to promote reliability of the steganography systems